Methodology for plotting the flight planned route change of the aircraft in flight - M. A. Kiselev; Y. S. Kalyuzhny; A. V. Karpov; S. F. Borodkin (Научный вестник МГТУ ГА)
A significant number of aviation incidents is related to loss of control in flight and controlled flight into terrain (LOC-I, CFIT, LALT categories). Investigation of these aviation incidents has revealed that these incidents often occur due to the need for rapid changes in flight routes as a result of detecting obstacles, such as thunderstorms, along the aircraft's path. During the determination of alternative routes to circumvent the encountered obstacle, as well as during the implementation process of the chosen rerouted route, the flight crew makes errors due to increased psycho-physiological workload and time constraints. This article presents an approach to the automatic rerouting of the aircraft's flight route to avoid obstacles detected during flight. The algorithm proposed by the authors allows for evaluating the safety of the original route, calculating alternative route options to bypass the obstacles encountered during flight, verifying their feasibility considering the aircraft's flight technical characteristics and control parameter limitations, and selecting the optimal rerouted route based on specific criteria, such as minimizing the increase in the flight route length, reducing additional fuel consumption, time required for implementing the new flight route, etc. Examples of rerouting the flight route of a hypothetical aircraft with detected obstacles along the flight path are provided in the article to demonstrate the algorithm's functionality. It is shown, in particular, that in the considered example, the shortest route for obstacle avoidance is not optimal in terms of time. It is also demonstrated that the safety of flying along the identified alternative rerouted routes depends, among other factors, on the selected flight speed. Therefore, for each calculated rerouted route, the algorithm determines a range of speeds within which the implementation of the obtained rerouted route is possible. This highlights the complexity and non-triviality of the pilot's task of autonomously finding a safe obstacle avoidance route on board the aircraft.